The Influence of Transformational Leadership, Organizational Culture, and Job Satisfaction on Organizational Citizenship Behavior - Risya Nazhira Rahma; Betria Betria; Siti Maryam; Sandi Nasrudin Wibowo (Journal of Social Science, 2025)
This study aims to analyze the influence of transformational leadership, organizational culture, and job satisfaction on Organizational Citizenship Behavior (OCB) among employees of PERUMDA PDAM Tirta Giri Nata, Cirebon City. Using a quantitative research design, data were collected through questionnaires from a sample of 115 respondents selected via the Slovin formula from a population of 160 employees. The study employed SPSS version 25 for data analysis, including validity and reliability testing, classical assumption tests, multiple regression analysis, and hypothesis testing. The findings revealed that transformational leadership, organizational culture, and job satisfaction each have a significant and positive effect on OCB. Simultaneously, these three variables together explained 70.9% of the variance in OCB. The implications suggest that strong transformational leadership, a supportive organizational culture, and high levels of job satisfaction significantly enhance employees’ voluntary and constructive behaviors that go beyond formal job requirements. The novelty of this research lies in its integrated model that simultaneously assesses the effects of these three antecedents, expanding on prior studies which often examined these variables in isolation or through mediators. The study contributes practical insights for human resource management in government-owned utility companies by identifying key psychological and organizational levers for improving citizenship behaviors. Future research should explore mediating factors such as psychological empowerment or organizational commitment and apply this model in different organizational and cultural settings to enhance generalizability.